2022
DOI: 10.33392/diam.1812
|View full text |Cite
|
Sign up to set email alerts
|

Retrakcje w filozofii na podstawie bazy Retraction Watch w świetle wytycznych Komisji Etyki Publikacji

Abstract: Artykuł prezentuje wyniki analizy ilościowej i jakościowej zawiadomień o retrakcji w publikacjach z zakresu filozofii (o zasięgu globalnym) zawartych w Retraction Watch Database, z punktu widzenia zaleceń Komisji Etyki Publikacji. Pod względem ilościowym próba wynosi jedynie 0,48% rekordów w całej bazie, przez co trudno uznać ją za reprezentatywną dla dyscypliny, a tym bardziej niemożliwe jest uogólnienia wniosków na całą aktywność naukową. Statystyka wycofań publikacji może być jednak podstawą do studium przy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Plagiarism was mentioned as the reason for retraction in 67% of the retraction notices (but in many cases euphemisms such as ‘overlaps’ were used). In most of the remaining cases, the reason for retraction was not clearly expressed (Kubalica & Łyszczarz, 2022). Retractions because of false or fabricated data are uncommon in philosophy.…”
Section: Retractions In the Humanitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Plagiarism was mentioned as the reason for retraction in 67% of the retraction notices (but in many cases euphemisms such as ‘overlaps’ were used). In most of the remaining cases, the reason for retraction was not clearly expressed (Kubalica & Łyszczarz, 2022). Retractions because of false or fabricated data are uncommon in philosophy.…”
Section: Retractions In the Humanitiesmentioning
confidence: 99%
“…Studies have shown that retraction notices often lack a clear statement of why the article was retracted. For instance, cases of plagiarism are often vaguely described, and references to the plagiarized texts are lacking (Kubalica & Łyszczarz, 2022; Madlock‐Brown & Eichmann, 2015).…”
Section: Make It Easier For Authors!mentioning
confidence: 99%